NETWORK ANALYSIS ON THE IN SILICO ASSIGNED Y CHROMOSOME HAPLOGROUPS IN WESTERN BALKAN POPULATIONS - Emir Šehović; Adna Ašić; Mustafa Dogan; Ramazan Tunc; Damir Marjanović; Serkan Dogan (Genetics & Applications, 2018)
The region of Western Balkans has been inhabited since the Paleolithic era and was the route of the spread of farming from the Middle East to Europe during the Neolithic era. In the present study, Y-STR data from European populations have been used to construct median-joining networks. The study was performed using Whit Athey’s Haplogroup Predictor, Y Utility and Network 4 software packages to predict Y haplogroups, construct networks, perform clustering of closely related Y chromosomes and calculate time estimates between individual nodes. The results of the study imply that geographically close populations cluster together at both Balkan and European levels. It was observed that an elevated number of study populations and individual haplogroups increases the possibility that individuals of different ethnic background cluster within the same or neighboring clades of network. Subsequent time estimates, performed based on the mutation frequency between the ancestral node and its descendant nodes, revealed that I2a haplogroup within the Western Balkan region has the most compact clustering (age, estimated at 3109 years), followed by Hg E1b1b which has the second most compact clustering (4896 years). The obtained results are nonetheless in accordance with previously published research investigating the frequency of Y haplogroups based on Y-SNP variant frequencies, indicating that Western Balkan countries are mainly represented by I2a subclade (average for six countries 32.3%), followed by E1b1b and R1a (average for six countries of 21.5% and 17%, respectively).